PERAN KELOMPOK PETERNAK DALAM MENGEMBANGKAN KEBERDAYAAN PETERNAK SAPI PERAH (KASUS DI KABUPATEN BANDUNG) - Unang Yunasaf; Basita Ginting; Margono Slamet; Prabowo Tjitropranoto (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2008)
The objective of the research was to study the role of the group farmers especially in term of dynamic of the group farmers, empowerment of the dairy farmers, and their relationship. The sampling population is milk cooperative at Bandung district and target population are the dairy farmers as the members of the cooperative. Sample of research were collected by multistage sampling technique with the result that 4 cooperative and 120 person of dairy farmers. The relationship of the variables were tested by Spearman’s rank correlation. The results showed that the group of dairy farmers tend by the cooperative as instrument for improving production of milk of dairy farmers but no facility sufficient so the dairy farmers have empowerment. The dynamic group of farmers was low. The empowerment of dairy farmer was low, especially in the role of dairy farmers as manager and individual of autonomy. There was positive significant correlation between the dynamic group of farmers are empowerment of the dairy farmers.